Pengaruh Konsentrasi MDM (Mechanically Deboned Meat) Terhadap Karakteristik Sensori dan Kimia Bakso - Amalia, Lia; Putri, Fenia Apriliani; Mardiah, Mardiah; Kusumaningrum, Julia (Jurnal Ilmiah Pangan Halal, 2023)
Meatballs are generally made from beef or chicken, which are relatively expensive so it is necessary to substitute or substitute cheaper ingredients. An alternative that can be used is MDM (Mechanically deboned meat). The experimental design used was a completely randomized design (CRD) with one factor, namely MDM concentration of 40%, 50%, 60% and 70%. Sensory and hedonic quality tests were carried out using a line scale which was then analyzed using analysis of variance (ANOVA) and Duncan's advanced test with a 95% confidence interval. The selected products are then subjected to chemical analysis including testing for water, ash, protein and fat content. The product chosen is meatballs that are white and grey, have a non-fishy aroma, are meaty and chewy like meatballs. Treatment A4 (70% MDM : 30% Tapioca) was the most preferred treatment by panelists in terms of color, aroma, texture, taste and overall appearance. The selected MDM meatballs based on sensory and hedonic quality tests were A4 (70% MDM : 30% Tapioca) with chemical test results namely water content 66.38%, ash 1.39%, protein 7.54% and fat content 1.56% and HPP of IDR 432/item.